Prediction of Indonesia's international relationship post-Jokowi Term 2024: international political literacy Study - Amiruddin, Ahmad; Ayu Fita, Gia; Nata Saputra, Aco; Losi, Zainuddin; Nur Fiqhi Utami, Andi (Universitas Muhammadiyah Ponorogo, 2022)
This study aimed to obtain input and scientific evidence regarding Indonesia's foreign policy prediction after the Jokowi presidency in 2024. This study aims to understand what foreign policy will look like in the next presidential term. To discuss the topic of efforts to answer the problems of this study, this study obtained data from many reading sources such as international publications in the form of books, articles, reports, and newspapers. The collected data is then reviewed carefully, which involves a data coding system, sharp analysis, in-depth evaluation, and high interpretation so that we can conclude research answers with high validity and reality principles. Based on the data presentation and discussion, it can be concluded that Indonesia's foreign policy after Mr. Jokowi's tenure is a series of visions that describe how Indonesia interacts with foreign countries that regulate bilateral cooperation with the principle of free and active political economy.Another issue that Indonesia can predict is still being done, as stated in the country's constitution. In other words, there is no significant difference. Thus the results of this study are helpful for the parties, especially for educational use and policy making.